PROFIL KROMATOGRAFI LAPIS TIPIS MINYAK ATSIRI SEREH (Cymbopogon citratus) - Rani Prabandari (Universitas Harapan Bangsa Purwokerto, 2017)
Abstract. Rhodinol has been isolated from citronella oil. Isolation of lemongrass oil is done by using the distillation method. Samples used were citronella harvested for 6 months and 9 months. Silent phase used TLC plate slika gel F254 with a size of 2 x 10 cm and the mobile phase used was Toluen: Ethyl Acetate (93: 7). Results of Thin Layer Chromatography HRF profile obtained for experiment I (citronella harvesting age 6 months) 32, 77, 87 and Experiment II (lemongrass harvest age 9 months) respectively 25, 73, 81.